2012
DOI: 10.1038/nsmb.2423
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for recognition of 5′-phosphotyrosine adducts by Tdp2

Abstract: SummaryThe DNA repair enzyme TDP2 resolves 5′-phosphotyrosyl-DNA adducts, and is responsible for resistance to anti-cancer drugs that target covalent topoisomerase-DNA complexes. TDP2 also participates in key signaling pathways during development and tumorigenesis, and cleaves a protein-RNA linkage during picornavirus replication. The crystal structure of zebrafish TDP2 bound to DNA reveals a deep and narrow basic groove that selectively accommodates the 5′-end of single-stranded DNA in a stretched conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 39 publications
6
69
0
Order By: Relevance
“…5F). These results are consistent with the crystal structures for TDP2, showing the enzyme has a narrow DNA binding pocket, optimal for accessing single-stranded DNA ends (26,27).…”
Section: Ribonucleotide Incorporation Enhances Irreversible Top2cc Busupporting
confidence: 80%
See 2 more Smart Citations
“…5F). These results are consistent with the crystal structures for TDP2, showing the enzyme has a narrow DNA binding pocket, optimal for accessing single-stranded DNA ends (26,27).…”
Section: Ribonucleotide Incorporation Enhances Irreversible Top2cc Busupporting
confidence: 80%
“…2 and 4) and that mild Top2 denaturation (70°C heating) (see Fig. 3) also allowed TDP2 action indicates that the active catalytic site of TDP2 can accommodate relatively large polypeptides (26,27). This result is in line with the fact that TDP2 can process some substrates with a bulky 5Ј-tyrosyl end (25) and acts as the VPg unlinkase for picornavirus replication (36).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…2B). The preference of TDP2 for 5′ phosphotyrosyl bonds is consistent with recent X-ray data (27)(28)(29), but TDP2 also is active on 3′-substrates (20,26,30). Although TDP2 likely is the only enzyme of its kind (30), complete knockout of TDP2 in chicken DT40 cells and in mice was not lethal (20), possibly reflecting the power of redundancy in DNA repair.…”
supporting
confidence: 71%
“…It has also been reported that the multifunctional enzyme Tdp2 (also known as TTRAP or EAPII) is more efficient in catalyzing the resolution of 5Ј-phosphotyrosyl adducts than Tdp1 (39). However, Tdp2 is a member of the exonuclease-endonucleasephosphatase (or EEP) nuclease family that uses single Mg 2ϩ -dependent catalysis to cleave the 5-phosphotyrosine bond and functions in the nonhomologous end joining pathway (40,41). Thus, Tdp1 and Tdp2 constitute complementary DNA repair activities, with distinct reaction mechanisms (27,42,43).…”
Section: Discussionmentioning
confidence: 99%